Singlebeam raw data (EK60 entire dataset) of RV ALKOR during cruise AL575 - Mia Schumacher; Matthias Haeckel; Mark Schmidt (PANGAEA, 2025)
Raw water column data were collected aboard RV ALKOR during cruise AL575 using a Simrad EK60 single beam system, operable at 120, 70 and 38 kHz with an opening angle of 7°. It is well usable to detect rising gas bubbles in the water column and therefore primarily the 70 kHz and the 120 kHz system we used for good spatial resolution and (depth) range. EK80 is the data acquisition software which can also be used to replay already recorded data. Post-processing, e.g. for a 3D analysis fo the gas flares and their backscatter strength, has not been done but can be performed using e.g. ESP3, an open source software kindly provided by P. Escobar and his team at NIWA (Wellington, New Zealand). The expedition took place during 2022-06-28 – 2022-07-13 from Kiel to Kiel (Germany) in the North Sea. The major aim of AL575 - GEOSTOR leak are to investigate and contribute to the assessment of the mechanisms and potential risks of CO2 leakage along boreholes drilled through the sedimentary overburden above subseafloor storage formations in the North Sea. Data were recorded in the EEZs of UK and Germany. Sound velocity corrections were made using a hull-mounted sound velocity profiler. Please see the cruise report for details. The data are unprocessed and can therefore contain incorrect measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition and provision was done by GEOMAR and they are published according to the FAIR principles.